Forecasting the development of explosive leg power in youth soccer players - Bennett, N.; Woodcock, S.; Pluss, M. A.; Bennett, K. J. M.; Deprez, D.; Vaeyens, R.; Lenoir, M.; Fransen, J. (Science and Medicine in Football, 2019)
Purpose: Monitoring athletic development in youth soccer can help sporting professionals monitor athletic development and evaluate the effectiveness of training interventions. However, long-term follow up in talent development programmes in youth soccer is complicated. Therefore, the aim of this study was to forecast the developmental trajectories of explosive leg power in youth soccer players. Methods: Mixed effects regression models were used to forecast explosive leg power (countermovement (CMJ) and standing broad jump (SBJ)) in a longitudinal sample of 2201 youth soccer players from two high level Belgian acedemies and the Belgian National teams. Players were aged between 6 and 20 years (mean age = 13.04 ± 3.18 y) and were subdivided into three age cohorts (6-10, 11-15, and 16-20 y) for CMJ and two age cohorts (6-16, and 17-20 y) for SBJ. Results: This study was able to accurately forecast explosive leg power using different regression equations in each age cohort. Conclusions: Researchers, coaches, and sporting professionals can use these methods to either predict future explosive leg power from current performance measures, monitor the development of explosive leg power, or assess the effectiveness of training interactions aimed at altering predicted developmental trajectories.